Effect of honey on hepatotoxicity induced by antitubercular drugs in albino rats - Chandane, Rakhamaji D.; Jaju, Jugalkishor B.; Ghadlinge, Manik S.; Bhosale, Rama R.; Chandrakapure, Ajay R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Drug-induced hepatotoxicity is a potentially serious adverse effect of antituberculosis treatment (ATT) regimens containing isoniazid, rifampicin and pyrazinamide. Many in vitro and in vivo studies revealed that honey possess antioxidant property and hepotoprotective property but there is no systematic work available to test the effect of honey on antitubercular drugs induced hepatotoxicity in rats. Hence present study was carried out to explore the prophylactic and therapeutic effect of honey with its antioxidant activity against hepatotoxicity induced by antitubercular drugs (Isoniazid, Rifampicin and Pyrazinamide) in albino rats. Methods: Hepatotoxicity in rats treated with antitubercular drugs (Isoniazid, Rifampicin and Pyrazinamide) was studied by assessing parameters such as Serum alanine aminotransferase (ALT), Serum aspartate aminotransferase (AST), Serum total protein, Serum Malondialdehyde (MDA) and Serum Superoxide dismutase activity (SOD). The effect of Honey as co-administration and administration after establishment of hepatotoxicity on above parameter was investigated. These biochemical observations were supplemented by Histopathological examination of liver. Results: Honey significantly reversed changes in serum levels of AST, ALT, MDA, SOD, total protein and also histopathological changes produced by Antitubercular drugs. It was found that honey significantly prevented as well as reversed Antitubercular drugs induced hepatotoxicity and antioxidant activity. Conclusions: The results of present study show that honey has significant prophylactic and therapeutic value against antitubercular drugs induced hepatotoxicity.